The Principle of the Dialogue as a Basis for the Religious Pluralism - Valantiejūtė, Lina (Religija ir kultūra, 2011)
The main aim of this article is to show that the dialogue, primarily understood as a relation with the Other, allows us not only to essentially (re)interpret the dominating streams of understanding of inter-religious dialogue as a formal interaction between the religions as systems, but it also enables us to see the phenomena of religious pluralism as fundamentally dialogical. The concept of a dialogue as a dual relationship by Martin Buber combined with the philosophical insights of Emmanuel Levinas and the criticism of the concept of the dialogue as a cognitive relation allows us to reveal the internal paradox of the phenomena of religious pluralism (a fundamental demand for a non reductive quantity and diversity as well as need to control it) and to explain a possibility of engagement in an inter-religious dialogue.